Spillover effects of sustainable consumption: combining identity process theory and theories of practice. Issue 1 (1st January 2019) - Frezza, Marcia; Whitmarsh, Lorraine; Schäfer, Martina; Schrader, Ulf
Abstract: Work organizations that implement sustainability strategies can create supportive environments for the performance of sustainable routines. For instance, employers have the capacity to influence sustainable lifestyles of their employees by increasing spillover effects from workplaces to home settings. These circumstances provide a potential pathway to change routinized activities in different domains. We critically review sociological and psychological literature on practices of environmental relevance to better understand these spillover effects. These disciplines have contributions to make but are on their own insufficient to determine trajectories toward more sustainable (consumption) routines. This analysis thus considers both structural and individual dimensions of sustainable lifestyles. To advance analyses of spillover of routinized activities, we present a framework that combines theories of practice concepts (meanings, competencies, and material aspects) and principles of identity process theory (continuity, distinctiveness, self-esteem, and self-efficacy). Our framework aims to identify and assess spillover effects from the workplace to domestic settings. We show that work organizations can systematically provide the elements necessary for the performance of sustainable practices. The framework underpins methodological instruments to explain spillover effects (of sustainable consumption), equally encompassing individual and structural aspects.